Feasibility of measuring magnetic resonance elastography-derived stiffness in human thoracic aorta and aortic dissection phantoms - Adnan Hirad, MD, PhD; Faisal S. Fakhouri, PhD; Brian Raterman, BS; Ronald Lakony, BS; Maxwell Wang, MD; Dakota Gonring, MD; Baqir Kedwai, MD; Arunark Kolipaka, PhD; Doran Mix, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
Type B aortic dissection (TBAD) represents a serious medical emergency with up to a 50% associated 5-year mortality caused by thoracic aorta, dissection-associated aneurysmal (DAA) degeneration, and rupture. Unfortunately, conventional size-related diagnostic methods cannot distinguish high-risk DAAs that benefit from surgical intervention from stable DAAs. Our goal is to use DAA stiffness measured with magnetic resonance elastography (MRE) as a biomarker to distinguish high-risk DAAs from stable DAAs. This is a feasibility study using MRE to (1) fabricate human-like geometries TBAD phantoms with different stiffnesses, (2) measure stiffness in TBAD phantoms with rheometry, and (3) demonstrate the first successful application of MRE to the thoracic aorta of a human volunteer. AD phantoms with heterogenous wall stiffness demonstrated the correlation between MRE-derived stiffness and rheometric measured stiffness. A pilot scan was performed in a healthy volunteer to test the technique's feasibility in the thoracic aorta.